Understanding brain mechanisms of reactive aggression - Bertsch, Katja; Florange, Julian G.; Herpertz, Sabine (Current psychiatry reports, 2020)
To review the current literature on biobehavioral mechanisms involved in reactive aggression in a transdiagnostic approach.